Optimalisasi Program Pusat Kegiatan Belajar Masyarakat (PKBM) Dalam Menurunkan Angka Putus Sekolah di Desa Alue Dua Kota Langsa - Masitah; Erni Wiriani; Esti Alemia Puspita; Adi Ahmad (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
One of the key non-formal educational institutions contributing significantly to human resource development at the grassroots level is the Community Learning Activity Center (PKBM). PKBM offers a comprehensive range of educational services, including Early Childhood Education (PAUD), Functional Literacy (KF), Package A (equivalent to elementary school), Package B (equivalent to junior high school), Package C (equivalent to senior high school), Business Learning Groups (KBU), and is also equipped with Community Reading Gardens (TBM). The main objective of PKBM is to expand educational access, particularly for marginalized communities that have limited opportunities to participate in formal education. PKBM serves as a means of community empowerment by improving knowledge, skills, and fostering a positive mental attitude that supports personal development and economic advancement. This study employed a participatory approach, emphasizing the active role and involvement of community members as assisted partners. Findings reveal that the establishment of PKBM in Alue Dua Village was initiated by the aspirations of the local community, supported by organizers. The programs implemented not only provide alternative educational pathways but also serve as a platform for social and economic transformation. Thus, PKBM is expected to become a driving force in enhancing the quality of life and overall community welfare in a sustainable manner